A Utility-Based Rate Allocation of M2M Service in Heterogeneous Wireless Environments. (24th September 2013) - Huang, Yao; Tian, Hui; Zhang, Jie; Qin, Cheng; Wang, Zhibo
Abstract : This paper presents a dynamic adaptive machine-to-machine (M2M) service rate allocation scheme for optimum traffic distribution in heterogeneous wireless environments (HWEs). According to the M2M service characteristics, it proposes the utility function, which forms a convex optimization problem that maximizes the utility of M2M service and can be solved by the Lagrange multiplier. The simulation results show the proposed method convergence, and it can achieve load balance with maximized throughput and minimized cost.